Maternal performance after childbirth and its predictors: a cross sectional study - Masoumeh Choobdarnezhad; Leila Amiri-Farahani; Sally Pezaro (BMC, 2024)
Abstract Background and Objectives Birthing parents need to use specialized skills as the first caregiver of the newborn. Several factors may affect performance. Yet there is a paucity of research in this area, and evidence remains inconsistent. Consequently, this study aimed to determine maternal performance after childbirth and its predictors. Methods This cross-sectional study was conducted with those (n = 450) who had given birth (< two months) and been referred for the vaccination of their newborn. The multi-stage sampling method was carried out from April 2022 to February 2023. Participants who met the inclusion criteria completed a demographic and obstetric information questionnaire, along with the childbirth experience 2 (CEQ2), Barkin maternal performance and maternal self-efficacy scales. Multiple linear regression was used to investigate the predictive effect of the independent variables of childbirth experience, maternal self-efficacy, demographic and obstetric variables on the dependent variable of maternal performance. Results The mean age of the participants was 26.78 and the mean total score of maternal performance was 91.04 (0-120). The highest and lowest scores related to the 'maternal competence' and the 'maternal needs' domains, with mean score calculated at 77.51 and 72.81 respectively. 'Childbirth experience' and 'maternal self-efficacy' domains had a statistically significant relationship with maternal performance (P < 0.05). Among the predictive factors of maternal performance, the results of our linear regression demonstrated the variables of birth experience (B = 0.63), maternal self-efficacy (B = 1.53), spouse's employment status (B = 5.78 for worker level, B = 3.99 for employee level), the number of previous childbirth experiences (B = -8.46), frequency of receiving antenatal care (B = -6.68), length of stay in the birth suite (B = -2.22) and length of stay in the hospital (B = 2.84) remained in the model. 53.2% of changes in maternal performance can be explained by these independent variables. Conclusion The promotion of evidence-based, person-centered, and respectful perinatal care during pregnancy and childbirth are of paramount importance. Strategies to improve the experience of childbirth and self-efficacy are especially required to improve maternal performance in the postpartum period. Prenatal care aimed at improving maternal function after childbirth will be important in achieving this overall.